Muestreo de frutos de naranjo ´Valencia late´ (Citrus sinensis, L. Osbeck) para ajustar una metodología de evaluación fitosanitaria (MEF) de lotes cítricos comerciales - Mika, Ricardo Horacio (2016)
The phyosanitary evaluation method (MEF) is a systematic way to take data from commercial citrus plots. Its main objective is to identify and quantify factors affecting their yields and fruit quality. Complexity of factors involved makes this not a simple task. Knowing these factors and their proportion of involvement can improve decisionmaking tasks in citrus grove management. Aim of this work is to define a sampling methodology to assess fruit quality. This information would be also useful to improve the MEF sampling scheme. In this work, a modified version of MEF was applied conducting intensive sampling on two plots, A and B. Fruit yield and quality was evaluated in a third of the plants and fruits of both plots. Fruit diameter, commercial quality and up to four factors affecting it per fruit were measured or identified and registered. A baseline or "gold standard" problems detected was generated in order to apply Efron´s technique of resampling. Taking into account all the surveyed plants, thirty random resamplings without replacement were considered, one in two, one in three, and 8, 16 and 24 fruits per plant, respectively, completing nine sampling schemes. In plot A, the sampling scheme considering a plant among 6 and 8 fruits per plant showed no statistically significant differences compared to the "Gold Standard" value. Instead, in plot B, the high variability in the quality of plants and fruits did not allow to establish an effective sampling scheme. Using information generated by the method and applying geostatistical techniques, maps showing spatial distribution of yield, fruit quality and main factors affecting them within both plots could be developed. All this information can be also considered suitable to be used as a basic tool in precision fruit production.